PENGARUH PROYEK TRANS ASEAN GAS PIPELINES (TAGP) TERHADAP ARAH KEBIJAKAN LUAR NEGERI INDONESIA DI BIDANG KERJASAMA ENERGI TAHUN 2002-2015 - Larasaty, Dwiky (Global and Policy Journal of International Relations, 2017)
ABSTRACTASEAN has announced plans to construct a natural gas pipeline network through the Trans-ASEAN Gas Pipeline Infrastructure Project, or TAGP. Furthermore, the advocates of TAGP expect it to promote economic development, earn foreign exchange, mitigate the risks of climate change, and enhance regional energy security. Energy Security is also a system, composed of national policies and international institution, therefore it requires policies and a business climate that promote investment and development and innovation to ensure that adequate supplies and infrastructure will be available, in a timely way, and in the future. Afterwards, Indonesia as a led country in ASEAN which has a natural gas energy resources that are relatively large then considering the direction of Indonesia’s foreign policy to cooperate on the global system through cooperativeenergy governance framework. The direction of Indonesia’s foreign policy has basic optimistic to promote economic growth and embrace the ASEAN region to be more integrated.Keywords: ASEAN, TAGP, Energy Security, Indonesia’s Foreign Policy, Inter-regional Cooperation, Cooperative Energy GovernanceDOI : https://doi.org/10.33005/jgp.v5i01.1899